Manajemen Blended Learning Nilai Agama dan Moral pada Masa Pandemi di RA Masyitoh Mertasinga Cilacap Utara Kabupaten Cilacap - Nurchasanah Nurchasanah (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
The increasingly widespread spread of Covid 19 requires that learning in schools be carried out online. However, there are several institutions that carry out blended learning, namely carrying out limited online and face-to-face learning such as RA Masyitoh Mertasinga. Formulation of the problem, first how to plan a blended learning of Religious and Moral Values at RA Masyitoh Mertasinga, secondly how to implement blended learning of Religious and Moral Values at RA Masyitoh Mertasinga and third how to evaluate the blended learning of Religious and Moral Values at RA Masyitoh Mertasinga.This research is a qualitative research because it produces qualitative data. Collecting data using interviews, observation and documentation. Test the validity of the data using triangulation techniques. Data analysis used description techniques with the Miles and Huberman interaction analysis model with flows including data collection, data reduction, data presentation and drawing conclusions.The results of the study concluded, firstly the planning of blended learning on Religious and Moral Values at RA Masyitoh Mertasinga includes planning at the institutional level, namely preparing blended learning supporting facilities and infrastructure and planning at the teacher level, namely setting material, setting goals, setting strategies, methods and media, compiling a syllabus, establishing learning activities, planning evaluation and determining follow-up steps, the second is the implementation of blended learning, namely the delivery of material by the teacher to students through a series of activities to teach students actively, creatively, productively and fun by applying various strategies and methods and using media and teaching aids to achieve learning objectives and the third evaluation of blended learning includes evaluation of the implementation of blended learning and evaluation of student learning outcomes